2021
DOI: 10.5812/hepatmon.105632
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSTM1 and GSTT1 Null Deletions and GSTP1 rs1695 Polymorphism with the Risk of Hepatocellular Carcinoma: A Systematic Review and Meta-analysis

Abstract: Context: Hepatocellular carcinoma (HCC), as the most common type of primary liver cancer (accounting for 70% - 90% of all liver cancers), is the seventh most common malignancy worldwide. Glutathione S-transferases (GSTs) are a specific group of enzymes that are responsible for the detoxification of carcinogens. According to the available literature, genetic variations in this group of enzymes may be associated with the risk of HCC. In this study, we aimed to assess the association of GSTM1 and GSTT1 null delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…It is speculated that GSTM1 may affect the susceptibility to metastasis and invasion of breast cancer through the EMT pathway in terms of mechanism of action (18). To evaluate the association between GSTM1 and GSTT1 deletion and GSTP1 rs1695 polymorphism and the risk of liver cancer, studies found that the deletion of GSTM1 and GSTT1 increased the risk of liver cancer (19). It further supports the reliability of the conclusion that it is related to the susceptibility to GC.…”
Section: Discussionmentioning
confidence: 55%
“…It is speculated that GSTM1 may affect the susceptibility to metastasis and invasion of breast cancer through the EMT pathway in terms of mechanism of action (18). To evaluate the association between GSTM1 and GSTT1 deletion and GSTP1 rs1695 polymorphism and the risk of liver cancer, studies found that the deletion of GSTM1 and GSTT1 increased the risk of liver cancer (19). It further supports the reliability of the conclusion that it is related to the susceptibility to GC.…”
Section: Discussionmentioning
confidence: 55%